2004
DOI: 10.1021/jo049359m
|View full text |Cite
|
Sign up to set email alerts
|

Biphenol-Based Phosphoramidite Ligands for the Enantioselective Copper-Catalyzed Conjugate Addition of Diethylzinc

Abstract: Phosphoramidite ligands, based on ortho-substituted biphenols and a chiral amine, induce high enantioselectivities (ee's up to 99%) in the copper-catalyzed conjugate addition of dialkylzinc reagents to a variety of Michael acceptors. Particularly, the best reported ee's were obtained for acyclic nitroolefins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(59 citation statements)
references
References 22 publications
0
55
0
4
Order By: Relevance
“…[26] Die am häufigsten genutzte Synthese verläuft über das Chlorphosphit 10 (Weg A, Schema 2), das zunächst durch Reaktion des entsprechenden Diols 9 mit Phosphortrichlorid hergestellt und danach mit dem gewünschte Amin in Gegenwart einer Base umgesetzt wird. [26,31,32,62] Für die sterisch anspruchsvolleren Amine 12 bietet die Synthese des Di-chloraminophosphans 13 im ersten Schritt eine Alternative; [63] in diesem Fall wird das Amin zuerst mit Phosphortrichlorid umgesetzt, danach wird das entsprechende Diol zugegeben (Weg B, Schema 2). Ein dritter Syntheseweg beginnt mit der Reaktion von BINOL mit HMPT (Hexamethylphosphortriamid), bei der das Dimethylaminderivat des Phosphoramidit-Liganden L1, MonoPhos genannt, entsteht.…”
Section: Phosphoramidite: Struktur Synthese Und Eigenschaftenunclassified
See 2 more Smart Citations
“…[26] Die am häufigsten genutzte Synthese verläuft über das Chlorphosphit 10 (Weg A, Schema 2), das zunächst durch Reaktion des entsprechenden Diols 9 mit Phosphortrichlorid hergestellt und danach mit dem gewünschte Amin in Gegenwart einer Base umgesetzt wird. [26,31,32,62] Für die sterisch anspruchsvolleren Amine 12 bietet die Synthese des Di-chloraminophosphans 13 im ersten Schritt eine Alternative; [63] in diesem Fall wird das Amin zuerst mit Phosphortrichlorid umgesetzt, danach wird das entsprechende Diol zugegeben (Weg B, Schema 2). Ein dritter Syntheseweg beginnt mit der Reaktion von BINOL mit HMPT (Hexamethylphosphortriamid), bei der das Dimethylaminderivat des Phosphoramidit-Liganden L1, MonoPhos genannt, entsteht.…”
Section: Phosphoramidite: Struktur Synthese Und Eigenschaftenunclassified
“…[127,128] Später wurden Biphenol-Liganden mit verschiedenen Substituenten in 2-und 4-Stellung beschrieben. [63] Durch Variieren dieser Substituenten konnten bei der Addition von Dialkylzinkreagentien an eine Reihe von Michael-Akzeptoren ausgezeichnete ee-Werte und Ausbeuten erhalten werden. Die systematische ¾nderung der Substituenten an den Liganden ergab keine eindeutige Tendenz, die besten Ergebnisse lieferte der Ligand L16 (Abbildung 5).…”
Section: Neue Entwicklungenunclassified
See 1 more Smart Citation
“…Many efforts have been made in designing efficient systems and identifying new ligands to improve enantioselectivities. [1] Among the most efficient ligands, those based on the atropoisomerism [2] of a binaphthol [3] or a biphenol [4] moiety play a prominent role. We have demonstrated that phosphoramidite ligands based on the atropoisomerically flexible biphenol unit are also excellent ligands (Scheme 1).…”
mentioning
confidence: 99%
“…All chiral ligands were prepared according to the literature procedures (for ligands L1-L11, see references [26], [33], [47], and [48]; for ligands L12-L15, see references [49] and [50]; for ligands L16-L19, see reference [31]). Lithium bromide and lithium chloride were dried at 80 8C over 24 h prior to use.…”
Section: Methodsmentioning
confidence: 99%